Emotional difficulties in children with behaviour difficulties, within special education schools : submitted in fulfilment of the requirements for the Masters degree of Arts in Psychology at Massey University - Niehaus, Bernard Greeff (Massey University, 2010)
The aim of this study is to identify and address whether the symptoms of depression, anxiety and trauma are higher in children with behaviour difficulties than those in the general population of the same age and gender. A group of 22 children aged 8 – 13 of both genders participated in the research. The sample selected attend a special needs school for children classed as having behaviour difficulties. These children have been removed from mainstream education due to their behaviour. Literature points to the fact that the symptoms of depression, anxiety and trauma can affect the behaviour and academic ability of children. There is however very limited literature available on children with behaviour difficulties. The children completed a Child Depression Inventory, Multidimensional Anxiety Scale, and Trauma Symptoms Checklist for Children. The teacher and parents of these children completed a Conners behaviour checklist to establish a baseline of behaviour for these children. The asTTle academic records of the children were accessed from the school’s database to establish a baseline of academic achievement for these children in comparison to the general population. The research conducted indicated mixed results both indicating that children in these special needs school have both higher and similar rates of symptoms of depression, anxiety and trauma.
Keywords: Special needs; Depression in children; Anxiety in children; Trauma in children; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380104 Personality, abilities and assessment